LA NO RESPUESTA EN LAS ENCUESTAS - Droesbeke, Jean-Jacques; Lavalleé, Pierre (La Sociología en sus Escenarios, 2010)
Abstract. In the surveys it happens that it is impossible to obtain answer from the interviewed people for one or more variable than the survey tries to measure. One says then that one is in the presence of "nonanswers". When the survey uses questionnaires, the lack of values can come from multiple factors, for example, bad ignorance or, will fear survey its of the required subject, the negligence of the poll that does not strive so that each question obtains an answer, the type of question, the length of the questionnaire, etc. In other words, all absence of answer is considered here like nonanswer, anyone is its origin, is this refusal to respond or the loss of the data previously obtained. Resumen. En las encuestas ocurre que es imposible obtener respuesta de parte de los entrevistados para una o más variables que el survey procura medir. Se dice entonces que se está en presencia de "no respuestas". Cuando la encuesta utiliza cuestionarios, la falta de valores puede provenir de múltiples factores, por ejemplo, la mala voluntad, el temor del encuestado o su ignorancia del tema requerido, la negligencia del encuestador que no se esfuerza por que cada pregunta obtenga una respuesta, el tipo de pregunta, la longitud del cuestionario, etc. En otras palabras, se considera aquí como no respuesta toda ausencia de respuesta, cualquiera sea su origen, sea este la negativa de responder o la pérdida de la información anteriormente obtenida.